Pengaruh Harga Dan Promosi Terhadap Keputusan Pembelian Produk Chatime Mall Kelapa Gading Di Era Pandemi Covid 19 - Murdiyanto, Dono; Aritonang, Saida (Cv. Syntax Corporation Indonesia, 2022)
Purchasing decisions are fundamental to determining actions in purchasing a product, because it relates to consumer behavior at the stage before the purchase of a product. This is important because it relates to consumer decisions in determining which product to choose to make a purchase of the product. The existence of purchasing decisions is influenced by several factors including Marketing & price. and knowing the effect of price and promotion services marketing strategy simultaneously on the purchasing decisions of Chatime products. The type of research used is explanatory research with a quantitative approach. Then the results of this research can be concluded that.This means that purchasing decisions will increase if there are prices and promotions, and it is concluded that prices and promotions can influence purchasing decisions. Based on the results of the research conducted and the discussion that the author has described, it can be concluded that the Price and Promotion Variables affect the Purchase Decision Variable.